Structural and functional prediction of Leucosporidium antarcticum antifreeze protein (Afp1) - Zulkifli, Mohammad Fairuz (2010)
Under extreme temperature of frozen state, only a few type of protein can be survived which known as antifreeze protein (AFP). The AFP can prevent and control the ice growth within the cell and avoid the cell from damage. A novel antifreeze protein (Afp1), Leucosporidium antarcticum with 411 base pair was expressed in pET32b and used three different E. Coli host strains; BL21 (DE3), Origami (DE3) and RosettaGami (DE3). The Afp1 with 177 residues was subjected to template analysis but it failed and 54 random template of AFP was chosen and aligned multiple with ClustalW but still gave poor results. The sequence was then threaded with FUGUE, mGenthreader and 3DPSSM but unsatisfied score level obtained. Lastly, ab-initio I-TASSER (iterativethreading assembly refinement) method was applied and it produced five predicted models of Afp1; AFP1, AFP2, AFP3, AFP4 and AFP5. After evaluation process, AFP3 proposed the best results with the model of four alpha helices and two beta sheets. Almost 80% of the residues were located in the favoured regions which strongly support this predicted model. It also showed average score between 0.30-0.60 in the Verify3D analysis which is satisfying for a low percentage of similarity protein models. In the alpha helix segments, there were five major amino acids (serine, threonine, aspartic acid,asparagine and glutamine) which had high possibility to be bonded with the water molecule at the ice surface. Molecular Dynamics (MD) simulation was applied on the AFP3 model to find the optimum temperature for the Afp1 activity. The model was repaired by using Simulated Annealing (SA) before proceed to MD simulations at 273K, 277K and 283K at 3ns. The root mean square deviation (RMSD) and radius of gyration analysis showed that the model of Afp1 was most stable at 277K. Thus, this research managed to predict the Afp1 structure via ab-initio I-TASSER simulations and suggest that the structure of Afp1 had optimum activity at 277K.